1996
DOI: 10.1002/j.1556-6978.1996.tb00379.x
|View full text |Cite
|
Sign up to set email alerts
|

The Portfolio Emperor Has No Clothes: He Should Stay Naked

Abstract: Carney, Cobia, and Shannon (1996), and Baltimore, Hickson, George, and Crutchfield (1996) advocate the use of portfolio assessments in counselor education, but there is insufficient evidence that these are ethical means of assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…For example, tests used for screening decisions require less rigorous levels of consistency such as .80, but tests used for important decisions about individuals require the highest level of consistency as demonstrated by reliability coefficients of .90 or higher (Salvia & Ysseldyke, 2004). Alschuler (1996) concluded that there was no scientific evidence to support use of portfolios in university training programs for counselors. Although some studies have presented data with acceptable reliability (Naizer, 1997), most reported coefficients that ranged from .33 (Koretz, 1993) to .66 (Baxter, Shavelson, Goldman, & Pine, 1992), with increased interscorer coefficients of .76 to .89 with intense training (Gentile, 1990).…”
mentioning
confidence: 99%
“…For example, tests used for screening decisions require less rigorous levels of consistency such as .80, but tests used for important decisions about individuals require the highest level of consistency as demonstrated by reliability coefficients of .90 or higher (Salvia & Ysseldyke, 2004). Alschuler (1996) concluded that there was no scientific evidence to support use of portfolios in university training programs for counselors. Although some studies have presented data with acceptable reliability (Naizer, 1997), most reported coefficients that ranged from .33 (Koretz, 1993) to .66 (Baxter, Shavelson, Goldman, & Pine, 1992), with increased interscorer coefficients of .76 to .89 with intense training (Gentile, 1990).…”
mentioning
confidence: 99%
“…As part of the multiple methods that may be used in this process, portfolios can serve as a valuable tool to integrate clinical and academic experiences so as to provide assessment of a student's overall progress. To borrow Alschuler's ( 1996) words, "creating a portfolio of educational accomplishments could occupy a complementary role among other training methods, and perhaps be the crown in counselor education" (p. 136). Alschuler, we don't think we could have said it any better.…”
mentioning
confidence: 99%